Nocturnal Birds of Prey as Carriers of Staphylococcus aureus and Other Staphylococci - Silva, Vanessa (2022)
This work was funded by the R&D Project CAREBIO2: Comparative assessment of antimicrobial resistance in environmental biofilms through proteomics—towards innovative thera-nostic biomarkers, with reference NORTE-01-0145-FEDER-030101. This work was supported by the Associate Laboratory for Green Chemistry-LAQV, which is financed by national funds from FCT/MCTES and by the UIDB/CVT/00772/ 2020 project funded by the Portuguese Foundation for Science and Technology (FCT). Publisher Copyright: © 2022 by the authors. Licensee MDPI, Basel, Switzerland.